Relationship between Sources and Teachers' Sense of Efficacy among Novice Teachers in Selangor, Malaysia - Saw, Hooi Chin (2007)
This study attempts to investigate novice teachers' sources of efficacy in relation to the application of knowledge in Educational Psychology. The study is aimed to identify which particular source of efficacy information and other demographic factors, such as novice teachers' gender, ethnic group, subject matter knowledge best function as factors that instill higher efficacy beliefs among novice teachers. The two instruments used were the Teacher Sense of Efficacy Scale (TSES) developed by Tschannen-Moran and Woolfolk Hoy (2001), and the Sources of Teacher Efficacy Inventory (STEI) developed by the researcher. The questionnaires were administered to a sample of 160 novice teachers from 102 secondary schools in the District of Petaling and Klang in Selangor. The findings indicated that the novice teachers demonstrated a moderate level of teachers' sense of efficacy (M=3.85, SD=0.38). The majority of 66.9% novice teachers fall into the moderate level of teachers' sense of efficacy group. They also perceived a moderate level of all four sources of efficacy, namely mastery experience (M=3.58, SD=0.33), vicarious experience (M=3.82, SD=O.32), social persuasion (M=3.85, SD=0.32), and physiological or emotional arousal (M=3.61, SD=0.38). There was a strong and significant positive correlation between the mastery experience and teachers' sense of efficacy [r = 0.71, p < 0.05], a moderately low and significant positive correlation between the vicarious experience and teachers' sense of efficacy [r = 0.33, p < 0.05], a moderately strong and significant positive correlation between the social persuasion and teachers' sense of efficacy [r =0.46, p < 0.05J, and a weak but significant negative correlation between the physiological or emotional arousal and teachers' sense of efficacy [r = -0.17, p < 0.05]. There was no significant difference in novice teachers' sense of efficacy in relation to gender [t(158)=0.73, p>0.05)], ethnic groups [F(2,157)=0.42, p>0.05], and subject matter knowledge [t(158)=0.56, p>0.05]. This shows that the demographic variables do not affect teachers' senses of efficacy. The three sources of efficacy, namely mastery experience, vicarious experience, and social persuasion were identified as the predictors of teachers' sense of efficacy [Adjusted R2 = 0.50, F(3, 155) = 53.16, p<O.OI]. The implication of the study on the theory and practice of teachers' sense of efficacy was discussed. Suggestions and recommendations were offered to enhance and foster senses' of efficacy among the novice teachers.